Friedreich's Ataxia Frequency in a Large Cohort of Genetically Undetermined Ataxia Patients - Brown, Alexander F.; Parkinson, Michael H.; Garcia-Moreno, Hector; Mudanohwo, Ese; Labrum, Robyn; Sweeney, Mary; Giunti, Paola (Frontiers in Neurology, 2021)
Background: Patients with suspected genetic ataxia are often tested for Friedreich’s ataxia (FRDA) and/or a variety of spinocerebellar ataxias (SCAs). FRDA can present with atypical, late-onset forms and so may be missed in the diagnostic process. We aimed to determine FRDA-positive subjects among two cohorts of patients referred to a specialist ataxia centre either for FRDA or SCA testing to determine the proportion of FRDA cases missed in the diagnostic screening process. Methods: 2000 SCA-negative ataxia patients, not previously referred for FRDA testing (group A), were tested for FRDA expansions and mutations. This group was compared with 1768 ataxia patients who had been previously referred for FRDA testing (group B) and were therefore more likely to have a typical presentation. The phenotypes of positive cases were assessed through review of the clinical case notes. Results: Three patients (0.2%) in group A had the FRDA expansion on both alleles, compared with 207 patients (11.7%) in group B. The heterozygous carrier rate across both cohorts was of 41 out of 3768 cases (1.1%). The size of the expansions in the three FRDA-positive cases in group A was small, and their presentation atypical with late-onset. Conclusions: This study demonstrates that FRDA is very rare among patients referred purely for SCA testing without the clinical suspicion of FRDA. This study shows that in such cases it is not necessary routinely to extend genetic testing to include FRDA mutations. FRDA testing may be considered if SCA testing is negative and if there is clinical suspicion of late-onset FRDA.